Disseminated histoplasmosis with adrenal insufficiency in an immunocompetent adult – A case report (Indian Journal of Case Reports, 2020)
Histoplasmosis is a rare and potentially fatal disease caused by Histoplasma capsulatum. The occurrence of disseminated histoplasmosis in immunocompetent individuals is rare. The presentation of disseminated histoplasmosis as adrenal insufficiency is extremely rare and associated with significant mortality. We describe the case of a 49-year-old patient who presented with fatigability, postural hypotension, a large tongue ulcer, and hypoglycemia. The patient was found to have adrenal insufficiency and on evaluation was diagnosed as histoplasmosis. He was subsequently given antifungals and his adrenal insufficiency improved with treatment.